Detection and Characterization of a Reassortant Mammalian Orthoreovirus Isolated from Bats in Xinjiang, China - Xiaomin Yan; Jinliang Sheng; Chang Zhang; Nan Li; Le Yi; Zihan Zhao; Ye Feng; Changchun Tu; Biao He (Viruses, 2022)
Mammalian orthoreoviruses (MRVs) are increasingly reported to cause various diseases in humans and other animals, with many possibly originating from bats, highlighting the urgent need to investigate the diversity of bat-borne MRVs (BtMRVs). Here, we report the detection and characterization of a reassortant MRV that was isolated from a bat colony in Xinjiang, China. The BtMRV showed a wide host and organ tropism and can efficiently propagate the cell lines of different animals. It caused mild damage in the lungs of the experimentally inoculated suckling mice and was able to replicate in multiple organs for up to three weeks post-inoculation. Complete genome analyses showed that the virus was closely related to MRVs in a wide range of animals. An intricate reassortment network was revealed between the BtMRV and MRVs of human, deer, cattle, civet and other bat species. Specifically, we found a bat-specific clade of segment M1 that provides a gene source for the reassortment of human MRVs. These data provide important insights to understand the diversity of MRVs and their natural circulation between bats, humans, and other animals. Further investigation and surveillance of MRV in bats and other animals are needed to control and prevent potential MRV-related diseases.